The impact of hyperandrogenemia on pregnancy complications and outcomes in patients with PCOS: a systematic review and meta-analysis - Xiaohan Guo; Yingsha Yao; Ting Wang; Juanhong Wu; Ruoan Jiang (Taylor & Francis Group, 2024)
Background Polycystic ovary syndrome (PCOS) is a metabolic and reproductive disorder. Current research findings present conflicting views on the effects of different PCOS phenotypes on outcomes in pregnancy and for newborns.Methods This research study followed the guidelines of the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA). A thorough search of literature was carried out using the Cochrane Menstrual Disorders and Subfertility Group trials register, Web of Science, and EMBASE databases from their start to December 2023. The search focused on studies examining the links between hyperandrogenic and non-hyperandrogenic PCOS phenotypes and risks in pregnancy and neonatology. Odds ratios (ORs) and 95% confidence intervals (CIs) were computed using either a fixed-effects or random-effects model.Results Our analysis incorporated 10 research studies. Expectant mothers with a hyperandrogenic PCOS subtype had increased ORs for gestational diabetes mellitus (GDM) and preeclampsia (PE) compared to those with a non-hyperandrogenic PCOS subtype, with respective values of 2.14 (95% CI, 1.18-3.88, I2 = 0%) and 2.04 (95% CI, 1.02-4.08, I2 = 53%). Nevertheless, no notable differences were detected in ORs for outcomes like preterm birth, live birth, miscarriage, cesarean delivery, pregnancy-induced hypertension, small for gestational age babies, large for gestational age newborns, and neonatal intensive care unit admissions between pregnant women with hyperandrogenic PCOS phenotype and those without.Conclusions This meta-analysis highlights that the presence of hyperandrogenism heightens the risks of GDM and PE within the PCOS population. Healthcare providers ought to be aware of this connection for improved patient management.